PIN1 in Cell Cycle Control and Cancer - Cheng, Chi-Wai; Tse, Eric (Frontiers in Pharmacology, 2018)
Cell cycle progression is tightly controlled by many cell cycle-regulatory proteins that are in turn regulated by a family of cyclin-dependent kinases through protein phosphorylation. The peptidyl-prolyl cis/trans isomerase PIN1 provides a further post-phosphorylation modification and functional regulation of these CDK-phosphorylated proteins. PIN1 specifically binds the phosphorylated serine or threonine residue preceding a proline (pSer/Thr-Pro) motif of its target proteins and catalyzes the cis/trans isomerization on the pSer/Thr-Pro peptide bonds. Through this phosphorylation-dependent prolyl isomerization, PIN1 fine-tunes the functions of various cell cycle-regulatory proteins including retinoblastoma protein (Rb), cyclin D1, cyclin E, p27, Cdc25C and Wee1. In this review, we discussed the essential roles of PIN1 in regulating cell cycle progression through modulating the functions of these cell cycle-regulatory proteins. Furthermore, the mechanisms underlying PIN1 overexpression in cancers were also explored. Finally, we examined and summarized the therapeutic potential of PIN1 inhibitors in cancer therapy.